Combination approach using neoadjuvant therapy with radical prostatectomy for improving oncological outcomes of high-risk prostate cancer: a narrative review - Nakane, Keita; Kawase, Makoto; Kato, Daiki; Iinuma, Koji; Kawase, Kota; Takeuchi, Shinichi; Tobisawa, Yuki; Ito, Takayasu; Koie, Takuya (Translational cancer research, 2024)
Prostate cancer (PCa) is the most common cancer in men. High-risk PCa is associated with an increased risk of PCa-related death. The combined use of androgen deprivation therapy (ADT) is essential to improve oncological outcomes in patients with high-risk PCa, and relatively long-term ADT administration is preferred when radiotherapy is performed. Meanwhile, whether neoadjuvant therapy for radical prostatectomy (RP) improves oncological outcomes remains controversial. This study aimed to review the oncological outcomes of RP in high-risk PCa and emphasize the significance of neoadjuvant therapy including neoadjuvant hormonal therapy (NHT) and neoadjuvant chemohormonal therapy (NCHT) followed by RP for managing high-risk PCa. We searched for articles published in the PubMed and Scopus databases from January 1, 2005 to March 30, 2023 using the medical subject headings (MeSH) terms: prostate cancer, prostatectomy, radiation therapy, neoadjuvant therapy, and treatment outcome. The study on NHT before RP for high-risk PCa found that NHT was associated with reduced adverse pathological features, such as pT3, positive surgical margins (PSM), and lymph node involvement. However, despite shorter operative times and improved surgical outcomes, NHT did not significantly enhance biochemical recurrence (BCR) or other oncological outcomes. The combination therapy using ADT and androgen receptor signaling inhibitors (ARSI) showed varying results. Another investigation explored NCHT with taxane-based agents, indicating acceptable treatment benefits and improved BCR-free survival rates in high-risk PCa patients, demonstrating potential feasibility for this approach. Ongoing trials, like the PROTEUS trial, aim to further evaluate the therapeutic efficacy of neoadjuvant therapy in high-risk PCa. NHT for high-risk PCa does not contribute to improved oncological outcome and should not be administered easily for downstaging or PSM reduction. NHT in combination with ARSI has the potential advantage of improving the oncological outcome of high-risk PCa compared to RP alone, but the results are currently unsatisfactory, and the development of individualized treatment strategies using several different therapeutic approaches is needed.